The Cambridge Companion to Paradise Lost / Ed. - Schwartz, Louis (New York : Cambridge University Press, 2014)
"This Companion presents fifteen short, accessible essays exploring the most important topics and themes in John Milton's masterpiece, Paradise Lost. The essays invite readers to begin their own independent exploration of the poem by equipping them with useful background knowledge, introducing them to key passages, and acquainting them with the current state of critical debates. Chapters are arranged to mirror the way the poem itself unfolds, offering exactly what readers need as they approach each movement of its grand design. Essays in Part I introduce the characters who frame the poem's story and set its plot and theological dynamics in motion. Part II deals with contextual issues raised by the early books, while Part III examines the epic's central and final episodes. The volume concludes with a meditation on the history of the poem's reception and a detailed guide to further reading, offering students and teachers of Milton fresh critical insights and resources for continuing scholarship"--
Machine generated contents note: Part I: 1. Milton as narrator in Paradise Lost Stephen M. Fallon; 2. Satan Neil Forsyth; 3. Things of darkness: sin, death, chaos John Rumrich; 4. The problem of God Victoria Silver; Part II: 5. Classical models Maggie Kilgour; 6. Milton's Bible Jeffrey Shoulson; 7. The line in Paradise Lost John Creaser; 8. The pre-secular politics of Paradise Lost Paul Stevens; 9. Cosmology Karen L. Edwards; Part III: 10. Imagining Eden William Shullenberger; 11. Milton's angels Joad Raymond; 12. Gender Shannon Miller; 13. Temptation W. Gardner Campbell; 14. Regeneration in Books 11 and 12 Mary C. Fenton; Part IV: 15. Reception William Kolbrener.
Keywords: LITERARY CRITICISM / European / English, Irish, Scottish, Welsh